The singular provincialization of the last national territory - D’Eramo, Daniel (Universidad Nacional del Litoral, 2021)
The authors have been developing a series of texts aimed at highlighting the Fuegian originality within the framework of the common features that the history of the Patagonian National Territories have. For this, an ad hoc periodization has been developed, which divides Patagonian and Fuegian history into three stages. The first, characterized by a not very extended and deep occupation of the territory by the State. The second, where the diminished impact, in the Fuegian sphere, of the state actions designed for Patagonia during a good part of the 20th century stands out. Finally, a third stage characterized by a dynamic of accelerated growth under the impulse of developmental policies, applied with a delay of decades with respect to the rest of the region. In short, to a highlight the social, economic and political singularity of Tierra del Fuego with respect to the situation of the rest of the Patagonian National Territories, is that this work is dedicated.